Factors Affecting Postoperative Functional Outcomes in Older Patients with Hip Fractures at a Large Public Hospital in Thailand - Chongmuenwai, Adisorn; Silathong, Phumin; Rattanakitkoson, Tana; Sukpongthai, Thanyaphon; Permthongchoochai, Nualchavee (Journal of Southeast Asian Orthopaedics, 2023)
Purpose: To identify prognostic factors for 6-month postoperative functional outcomes in older patients with hip fractures. Methods: This single-center prospective cohort study was conducted from January 2020 to December 2020. Patient factors and the preinjury Barthel index were collected from the patients at admission. The Barthel index was assessed again 6 months postoperatively to define functional outcomes. Minimal clinically important differences (MCIDs) between preinjury and 6-month functional outcomes were used to classify patients into satisfactory or unsatisfactory groups. The 6-month mortality rate was evaluated. Multiple logistic regression was used to analyze prognostic factors for postoperative functional outcomes. Results: In total, 320 patients were included in the analysis. The 6-month mortality rate was 11.8%. The average age and body mass index were 75.74±10.53 years and 20.98±3.96, respectively. Of the patients, 243 were female (75.94%), 210 were diagnosed with intertrochanteric fractures (65.83%), and 54 underwent surgery within 72 h (16.88%). In total, 249 patients (77.81%) had no complications. Multivariate analysis indicated that a time to surgery of < 72 h (odds ratio, 10.51; 95% confidence interval (CI), 5.42 to 20.37; p-value <0.01) was a significant prognostic factor for a satisfactory 6-month outcome. Conclusions: Time to surgery is a prognostic factor for a satisfactory functional outcome. Early surgery results in better functional outcomes in older patients with hip fractures.